Las élites de Santiago de Guatemala y el cabildo colonial, 1700-1770 - Santos Pérez, J. Manuel (1998)
This essay examines  the relations between the elite of Santiago de Guatemala and the cabildo (municipal council) of that city between 1700 and 1770.